Subcellular co-localization of Arabidopsis RTE1 and ETR1 supports a regulatory role for RTE1 in ETR1 ethylene signaling - Dong, Chun-Hai (2007)
Ethylene is an important plant growth regulator perceived by membrane-bound ethylene receptors. The ETR1 ethylene receptor is positively regulated by a predicted membrane protein, RTE1, based on genetic studies in Arabidopsis. RTE1 homologs exist in plants, animals and protists, but the molecular function of RTE1 is unknown. Here, we examine RTE1 expression and subcellular protein localization in order to gain a better understanding of RTE1 and its function in relation to ETR1. Arabidopsis plants transformed with the RTE1 promoter fused to the β-glucuronidase (GUS) reporter gene revealed that RTE1 expression partly correlates with previously described sites of ETR1 expression or sites of ethylene response, such as the seedling root, root hairs and apical hook. RTE1 transcript levels are also enhanced by ethylene treatment, and reduced by the inhibition of ethylene signaling. For subcellular localization of RTE1, a functional RTE1 fusion to red fluorescent protein (RFP) was expressed under the control of the native RTE1 promoter. Using fluorescence microscopy, RTE1 was observed primarily at the Golgi apparatus and partially at the endoplasmic reticulum (ER) in stably transformed Arabidopsis protoplasts, roots and root hairs. Next, a functional ETR1 fusion to a 5xMyc epitope tag was expressed under the control of the native ETR1 promoter. Immunohistochemistry of root hairs not only showed ETR1 residing at the ER as previously reported, but revealed substantial localization of ETR1 at the Golgi apparatus. Lastly, we demonstrated the subcellular co-localization of RTE1 and ETR1. These findings support and enhance the genetic model that RTE1 plays a role in regulating ETR1.